Identifying Incidence of and Risk Factors for Fluoroscopy-Guided Lumbar Puncture and Subsequent Persistent Low-Pressure Syndrome in Patients With Idiopathic Intracranial Hypertension. Issue 2 (June 2019) - Lu, Patricia; Goyal, Manu; Huecker, Julia B.; Gordon, Mae O.; Van Stavern, Gregory P.
Abstract : Background: To explore the incidence of and potential risk factors for developing persistent low-pressure syndrome after lumbar puncture (LP) in patients with idiopathic intracranial hypertension (IIH), as measured by use of blood patches. Methods: A retrospective chart review was conducted of patients with definitively diagnosed IIH by clinical examination and LP, comparing them to patients with multiple sclerosis (MS) as controls who also received diagnostic LPs. Demographic, clinical, and radiological data were collected for each patient. The main outcome measure was the rate of post-LP blood patches in IIH patients compared with MS patients. Secondary outcome measures were the likelihood of undergoing an epidural blood patch related to age, body mass index, volume removed, opening pressure, the difference between opening and closing pressure, and the level of puncture within the IIH cohort. Results: One hundred four IIH patients and 149 MS patients were included in the study. Among IIH patients, 12/104 (11.5%) underwent an epidural blood patch after LP as compared to 8/149 (5.4%) of the MS control patients ( P = 0.086). Within the IIH population, none of the clinical or LP parameters were significantly correlated with increased risk of needing a blood patch. Conclusions: The incidence of low-pressure syndrome, as measured by blood patches, is similar in IIH patients and MS controls. This suggests that having elevated intracranial pressure before an LP is not protective against developing postpuncture low-pressure syndrome, contrary to common assumptions.